Citogenetične in molekularnogenetične preiskave pri ugotavljanju kronične mieloične levkemije in spremljanju zdravljenja - Podgornik, Helena (Zdravniški vestnik, 2004)
Background. Chronic myeloid leukemia serves as a model for the disease where the knowledge as well as the development of different new methods from molecular biology were successfully introduced into the clinical practice. Methods. Standard cytogenetic analysis were primarily used for detecting the translocation between chromosomes 9 and 22: t(9;22) while fluorescence in situ hybridization (FISH) and real time PCR (Q-RT-PCR) were mainly employed for monitoring of the disease. We evaluated the results of both molecular diagnostic methods. During the past few years the work has been done in the laboratory of the Department for haematology in Ljubljana and Laboratory for Medical Genetics in Maribor. Results. A good correlation of results obtained by both meyhods was confirmed for the period of time before the complete cytogenetic remission. We also established an initial BCR-ABL/ABL ratio of 0.94 which is a basis for later determination of a major molecular remission which is defined as >/- 3 log reduction in BCR-ABL/ABL. Conclusions. Standard cytogenetic analysis of bone marrow cells is basic diagnostic approach in haematologic malignancies. At the same time FISH and PCR can also be used for confirmation of recurrent chromosomal abnormalities. FISH is the most appropriate method for CML monitoring during the first period of therapy. When cytogenetic remission is achieved, Q-RT-PCR is a method of choice. In acute leukemia PCR is mainly used in remission for the detection of malignant clone. If the clone can not be detected even by nested RT-PCR, prognosis of the disease is rather good.
Keywords: Citogenetična preiskava; Cytogenetic analysis; In situ hibridizacija, fluorescenčna; In situ hybridization, fluorescence; Leukemia, myeloid; Levkemija, mieloidna; Polimerazna verižna reakcija; Polymerase chain reaction